RETRACTION: ANANAS SATIVA INCREASES LONGEVITY THROUGH OXIDATIVE STRESS RESISTANCE IN DROSOPHILA MELANOGASTER - Ajagun-Ogunleye, M.O (African Journal of Traditional, Complementary and Alternative Medicines, 2018)
Background: Ageing is the major risk factor for most non-communicable diseases. It occurs as a result of free radical damage to macromolecules in the cell, coupled with environmental stress assaults. In the quest to identify new anti-ageing bioactive compounds from natural products, and despite the therapeutic values of Ananas sativa, its anti-ageing activity has not been fully elucidated. Therefore, the aim of this study was to screen the crude, methanol fruit extract of Ananas sativa (MEAS) and its fractions, for anti-ageing bioactivity in the fruit fly, Drosophila melanogaster w1118 wild type flies.Materials and Methods: Flies reared on food supplemented with 5, 10, and 20mg/ml fruit pulp and juice extract were assayed for longevity, fertility and stress resistance according to established protocols. Phytochemical composition and scavenging activity of extract on 2,2-diphenyl-1-picrylhydrazyl free radical (DPPH) were equally evaluated. The crude extract anti-ageing activity was assayed through a successive bioassay-guided fractionation approach, with different extraction solvents; n-Hexane, Chloroform, Ethyl acetate and Acetone.Results: There was a dose-dependent effect of the fruit extract on lifespan, fertility and oxidative stress resistance, with a unique information on the anti-ageing bioactivity of Ananas sativa. The IC50 values of the fruit extract and Ascorbic acid positive control in the free radical scavenging activity were 248.15μg/ml and 81.51μg/ml respectively. However, the bioactive fraction obtained from the Ethylacetate fraction F1, did not exhibit oxidative stress resistant effect in the model organism.Conclusion: The methanol fruit extract of Ananas sativa possesses anti-ageing bioactivity through oxidative stress resistance.